State Funding for Human Rights Activism: Channeling Protest?. (November 2017) - Clément, Dominique
Channeling theory posits that external funding for social movements, rather than coopting activism, channels activism into more structured and less militants forms. Studies on channeling, however, focus on private funding. The following article examines whether public funding has a comparable effect on social movements. Using the human rights movement in Canada as a case study, it examines several issues relating to channeling: why funders support activism; funding as social control or altruism; how funding is related to consolidating movement gains; and the impact of funding on mobilization, activism, and internal movement dynamics. To address these questions, this article draws on an innovative new data set that includes lists of grants extracted from more than 30 years of government budgets in Canada. It also draws on several years of archival research on a network of 19 organizations in every region of Canada, as well as interviews with former members of these organizations. In addition to demonstrating that public funding has a comparable channeling effect as private funding, this article provides the first comprehensive survey of the extent of state funding for the human rights movement in Canada.